INTENSIFIKASI PENINGKATAN WAJIB PAJAK DALAM MEMBAYAR PBB P2 DI BPK-AD KECAMATAN TUMPANG KABUPATEN MALANG - Lein, Maria Anita Goreti; Rahayu, Yayuk Ngesti (Manajemen & Bisnis Jurnal, 2021)
In summary, this study aims to analyze efforts to increase taxpayers in paying land and property taxes (PBB) on the basis of the collection system guided by Law No. 28 of 2009 (1) the collect local taxes in the payment of services or the issuance of certain permits provided by local governments or for personal or corporate interests; (2) Is a regional tax, administered by the Regional Revenue Authority, and its collection is based on rate rules set forth by the local government; (3) Collecting a regional tax as a tax may confer a better socioeconomic advantage or position on beneficiaries or entities or who derive an advantage from land and buildings. This study is a qualitative descriptive study. The informants for this study are the Services, Billing, General and Internal Compliance subsection, and the Advisory and Extension subsection at the Malang Regency Regional Property Administration. Data for this study were collected through interviews, documents, and observations. The results of this study indicate that (1) the compliance of taxpayers with the Regional Financial Asset Management Authority of Malang Regency sometimes increases and sometimes also decreases. As a result, the officers working at the Regional Property Management Authority of Malang Regency are working to increase taxpayers in paying land and property taxes